Ethnomathematics of Pananrang: A guidance of traditional farming system of the Buginese community - Pathuddin, Hikmawati; Kamariah; Mariani, Andi (Journal on Mathematics Education, 2023)
Culture plays an essential role in the emergence and development of mathematics; hence, both are inseparable. Mathematics emerges from the daily activities of a group of people, and although its concepts have been applied traditionally since time immemorial, it has not reached the level of formal usage. One cultural activity involving mathematical concepts is the use of Pananrang in determining the right farming seasons despite not having a formal education. Therefore, this research explores mathematical concepts in Pananrang, which are used as a reference for the Buginese community's farming system. This is qualitative research comprising an ethnographic approach with data collected through literature research and interviews with informants with expertise in Pananrang. The results showed that the community used mathematical concepts, such as multiplication, addition, and modular arithmetic, to determine the proper farming seasons. These outcomes can be socialized and used as a contextual learning resource.